2016
DOI: 10.22146/jag.26953
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical and Geochemical Control of Altered Andesitic Tuff upon Debris Slide Occurences at Pelangan Area, Southern Mountain of Lombok Island, Indonesia

Abstract: Debris slides were recently found in the Pelangan area at Southern Mountain of Lombok Island, Indonesia. Pelangan is well known as the gold mineralization and hydrothermal alteration area. This study is aimed to identify the mineralogy and geochemistry of altered andesitic tuff that controlled slope instability and induced debris slides. For this purpose, it is necessary to prepare the field observation and laboratory analyses. Landslide inventory reveals that the Pelangan debris slides mostly occur in altered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…On the other hand, based on previous research, Smectite mineral group as one of the main clay minerals found in this study also known by its swelling or expanding properties. This expanding property later is expected as the minerals that have strong influence to landslide susceptibility in argillic alteration area because it can break rock bonds [12]. Smectite group minerals are found in all locations in the study area.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…On the other hand, based on previous research, Smectite mineral group as one of the main clay minerals found in this study also known by its swelling or expanding properties. This expanding property later is expected as the minerals that have strong influence to landslide susceptibility in argillic alteration area because it can break rock bonds [12]. Smectite group minerals are found in all locations in the study area.…”
Section: Discussionmentioning
confidence: 72%
“…In several cases, the presence of hydrothermal activity is often related to the landslide event [12] have resulted in that clay minerals in the hydrothermally altered area could affects the landslide susceptibility. Ludovic et al (2004) [11] conclude that clay minerals influenced the rocks by increasing it pore pressure of water by increased porosity and low permeability.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The clay fraction resulted from further weathering of pyroxene [(Mg, Fe) 2 Si 2 O 6 ] minerals sourced from andesitic rocks. The increased content of montmorillonite and illite clay minerals from weathering of andesitic tuff rocks resulted in the occurrence of debris slides in the Pelangan Area, Lombok, Indonesia 29 .…”
Section: Soil Micromorphology Characteristic Of Lulcmentioning
confidence: 99%
“…The sliding surface's potential in the geothermal area consists of a clay layer dominated by the mineral of halloysite and metahalloysite [16]. Besides, montmorillonite clay minerals in the geothermal area also contribute to the landslide due to their swelling potential [17]. A significant landslide in the altered hydrothermal area is mostly related to argillic alteration when medium to small landslides mainly occur in prophylitic alteration [18].…”
Section: Introductionmentioning
confidence: 99%